2015
DOI: 10.1002/adma.201503565
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Assembled Wound Dressings Silence MMP‐9 and Improve Diabetic Wound Healing In Vivo

Abstract: The direct local delivery of short interfering RNA (siRNA) to tissues may present solutions to several complex medical conditions. In particular, chronic wound healing is a serious and painful complication of diabetes mellitus (DM) affecting as many as one in four patients with a three year recurrence rate of more than 50% and leaving over 70,000 patients in the United States alone facing amputation. Here we describe the use of siRNA delivered locally into the diabetic ulcer directly and in a sustained fashion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
147
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 205 publications
(153 citation statements)
references
References 62 publications
2
147
0
1
Order By: Relevance
“…4,5 In contrast to skin substitutes, 6 wound dressings are temporarily applied to the wound bed, in order to ensure a defined environment in terms of moisture (to minimise the risk of tissue maceration) and exudate management (to retain growth factors, MMPs and specific cells key to healing). 7,8 Furthermore, an ideal wound dressing should (i) provide thermal insulation and oxygen exchange; (ii) protect damaged tissue from secondary infections and bacterial contamination; (iii) display low adherence in situ to enable complete dressing removal without debris formation and integration with the host tissue; (iv) control activity of up-regulated MMPs, such as MMP-9, 9,10,11,12,13,14,15,16,17 in order to promote wound healing; (v) not induce any toxic response to tissue microenvironment. Although these requirements can be individually provided by many existing commercial dressings, such controlled multi-functionality is still challenging to accomplish in a single, soluble factor-free material system.…”
mentioning
confidence: 99%
“…4,5 In contrast to skin substitutes, 6 wound dressings are temporarily applied to the wound bed, in order to ensure a defined environment in terms of moisture (to minimise the risk of tissue maceration) and exudate management (to retain growth factors, MMPs and specific cells key to healing). 7,8 Furthermore, an ideal wound dressing should (i) provide thermal insulation and oxygen exchange; (ii) protect damaged tissue from secondary infections and bacterial contamination; (iii) display low adherence in situ to enable complete dressing removal without debris formation and integration with the host tissue; (iv) control activity of up-regulated MMPs, such as MMP-9, 9,10,11,12,13,14,15,16,17 in order to promote wound healing; (v) not induce any toxic response to tissue microenvironment. Although these requirements can be individually provided by many existing commercial dressings, such controlled multi-functionality is still challenging to accomplish in a single, soluble factor-free material system.…”
mentioning
confidence: 99%
“…55 As such, impregnating hydrogels and biomaterials with matrix metalloproteinase (MMP) inhibiting molecules or proteases is likely to positively affect wound healing by reducing degradation of growth factors within the wound. The primary mode of action for inhibiting MMPs is through the addition of a chelating agent, which binds to the active zinc sites on the MMPs, blocking its activity as a result.…”
Section: Matrix Metalloproteinase Inhibitionmentioning
confidence: 99%
“…3(a)]. 55 The delivery system developed by Castleberry et al could be extended to deliver a variation of siRNA for target wound treatment.…”
Section: Matrix Metalloproteinase Inhibitionmentioning
confidence: 99%
“…For instance, Breen et al reported that the topical delivery of adenovirus encoding endothelial nitric oxide synthase from a fibrin-based scaffold enhanced the production of nitric oxide and enabled faster re-epithelialization in a diabetic rabbit ulcer model [14]. In another study Steven et al, it knocked down the activity of matrix metallo protease (MMP) 9 by topical delivery of a siRNA in a diabetic rat wound model [15]. MMP play a major role in tissue remodeling during wound healing, but when overexpressed, these molecules delay the rate of wound closure.…”
Section: Recent Drug-eluting Systemsmentioning
confidence: 99%
“…Out of the 24 different types of MMPs, MMP 9 is extensively studied and found to be overexpressed in case of diabetic patients, which is a major reason for delayed healing of diabetic ulcers. Steven et al study showed that the topical delivery of SiRNA has enhanced the rate of wound healing and thereby has laid a foundation for delivery of SiRNA topically for chronic wound management [15].…”
Section: Recent Drug-eluting Systemsmentioning
confidence: 99%